Venous Thromboembolism after Orthopaedic Surgery – How Long is the Patient at Risk? - Nikhil Nanavati; Lee Hoggett; Matthew Hampton; Rathan Jeyapalan; Andrew Gordon (Journal of Aging Research And Healthcare, 2017)
Aim Venous thromboembolism (VTE) is a leading cause of morbidity and mortality in hospital with orthopaedic surgery already an established risk factor. This study aims to establish the length of time that a patient is at risk of sustaining a VTE post orthopaedic surgery. Method A retrospective case series of all patients who underwent orthopaedic surgery between 2010 and 2014 whom re-presented with a VTE within one year of their initial operation. Demographic, operative and clinical information was obtained in order to identify potential risk factors. Results 53 patients were identified as having a VTE within one year of discharge. The majority (63.4%) underwent lower limb arthroplasty. 29% of the cohort had either a family or personal history of VTE, 79% had ischaemic heart disease (IHD), hypertension or both. The average body mass index (BMI) of the cohort was 31.4; above the UK national average. 56.6% of the cohort developed a pulmonary embolism (PE) and 49% developed a deep vein thrombosis (DVT). Co-occurring DVT and PE was diagnosed in 5.6% of patients. The average length of time for readmission for patients to re-present at hospital with a PE was 122 days (range 4-361) and 107 days (range 7 – 360) with a DVT. Conclusion This study confirms the existence of pre-established risk factors for developing VTE including obesity, personal and family history of DVT, cardiovascular disease and lower limb arthroplasty. These risk factors are recognised despite patients receiving post-operative thromboprophylaxis. The findings of this study extend the current research by suggesting that patients presenting with known risk factors of developing VTE may be at risk for longer than the current guidelines cover for the administration of thromboprophylaxis. We propose further studies are needed to identify any potential requirements for more extensive VTE prophylaxis in this population.
Keywords: Venous Thromboembolism